Population pharmacokinetic analysis of lenvatinib in healthy subjects and patients with cancer - Gupta, Anubha (Br J Clin Pharmacol, 2016)
AIMS: Lenvatinib was recently approved for the treatment of radioiodine‐refractory differentiated thyroid cancer (RR‐DTC). Here, we characterized the pharmacokinetic (PK) profile of lenvatinib and identified intrinsic and extrinsic factors that explain interindividual PK variability in humans. METHODS: This population PK analysis used pooled data from 15 clinical studies, including eight phase 1 studies in healthy subjects, four phase 1 studies in patients with solid tumours, two phase 2 studies in patients with thyroid cancer and one phase 3 study in patients with RR‐DTC. RESULTS: The final pooled dataset included data from 779 subjects receiving 3.2–32 mg oral lenvatinib, mainly once daily as tablets or capsules. Lenvatinib PK was best described by a three‐compartment model with linear elimination. Lenvatinib absorption was best described by simultaneous first‐ and zero‐order absorption. The population mean value for lenvatinib apparent clearance (CL/F) was 6.56 l h(−1) [percent coefficient of variation (%CV) 25.5], and was independent of dose and time. The relative bioavailability of lenvatinib in capsule form was 90% vs. tablets (%CV 30.2). The final PK model included significant but marginal effects of body weight (2.8% of CL/F variation), liver‐function markers [alkaline phosphatase (−11.7%) and albumin (−6.3%)] and concomitant cytochrome P450 3A4 inducers (+30%) and inhibitors (−7.8%) on lenvatinib CL/F. Lenvatinib PK was unaffected by pH‐elevating agents, dose, age, sex, race, alanine aminotransferase, aspartate aminotransferase or bilirubin levels, or renal function. CONCLUSIONS: The significant effects of several covariates on lenvatinib PK variability were small in magnitude, and therefore were not considered clinically relevant, or to warrant any dose adjustment.